IMPROVING INVESTMENT LITERACY TO PREVENT FRAUDULENT INVESTMENTS AMONG TEMAS BATU PKK MOTHERS: PENINGKATAN LITERASI INVESTASI UNTUK MENCEGAH INVESTASI CURANG DI KALANGAN IBU-IBU PKK TEMAS BATU - Lusi Kurnia (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Cases of fraud disguised as investment schemes, which have caused losses to victims up to 2025, still show high numbers in Batu City, such as fraudulent housing schemes causing losses of hundreds of millions, and fraudulent arisan schemes among mothers, highlighting the importance of financial literacy for the community in Batu City. Objective: This activity aims to improve investment literacy among mothers at PKK Temas, Batu City, in order to avoid fraudulent investments. Method: The activity, conducted on November 20, 2025, involving 23 participants and organized in collaboration with Temas Subdistrict, combined interactive lecture methods with field simulations to ensure a comprehensive understanding of the material presented. Results: There was an increase in the average knowledge regarding fraudulent investments after receiving education on investment. Among the 23 participants, after receiving socialization and simulation, the average post-test score sharply increased to 8.65. This average score improvement of 4.13% resulted N-Gain value of 0.75, which is categorized as high effectiveness. Conclusion: Investment literacy among PKK Temas mothers in Batu City improved after the educational activity. As a follow-up, collaboration with PKK administrators can be conducted to regularly share updates on fraudulent investment cases in Batu City and maintain participants’ awareness.